Island mining: a look at the planning to successfully close and rehabilitate Mount Gibson’s Koolan Island mine - King, J; Temple-Smith, D; Devenny, J; Kershaw, E (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
According to Geoscience Australia (2024a) over 350 mine sites are operating in Australia, of which only five are located on an island (Geoscience Australia 2024b). Many of the closure considerations for an island-based mining operation are like those on the mainland; however, island-based mine sites face several challenges that are not commonly found in more traditional mining landscapes. Koolan Island has been mined for iron ore since the early 1900s, with BHP setting up the first large-scale mining operation in the 1960s before closing it in 1993. The modern-era mine is owned and operated by Koolan Iron Ore Pty Ltd (a wholly owned subsidiary of Mount Gibson Iron Limited). Main Pit on Koolan Island is directly adjacent to Yampi Sound and has a terminal depth of approximately 200 m below mean sea level. An engineered seawall buttressed by surrounding country rock constrains entry of seawater into the open pit. Closure planning for Main Pit presents several interesting challenges that include redesigning the seawall fascia to meet stable post-closure specifications and designing an engineered trench allowing flooding of Main Pit to create a tidally fluxed, aerobic lake restoring habitat for native local marine biodiversity (including hard corals) in the photic zone. The Traditional Owners, the Kimberley Dambimangari community, have a strong connection with Koolan Island as country with determined native title rights. Upon closure of the mine there is a will to establish occupancy and a presence on Koolan Island. This post-mining land use requires purposeful engagement and planning to provide a safe and sustainable place to live, work and recreate. Achieving this post-mining land use in an island setting is complex, requiring high-level logistics to ensure that basic resources including food, water and electricity continue to be available. While closure planning for Koolan Island is ongoing, the objective of this paper is to explore the inventive problem-solving concepts needed to successfully implement mine closure for an island landscape to meet the expectations of the company, stakeholders and regulatory agencies.
Keywords: logistics